2017
DOI: 10.4102/sajhivmed.v18i1.718
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of caregiving on the family caregivers of chronically ill AIDS and/or HIV patients in home-based care: A qualitative study in Zimbabwe

Abstract: Background: The family caregiver has a pivotal role to play in the management of the chronically ill HIV and/or AIDS patients. The wellbeing of caregivers is therefore crucial because impairment of their physical or mental health could impact negatively on the management of their HIV-positive family member. The purpose of this qualitative study was to explore the psychosocial impact of caregiving on the family caregiver of the chronically ill HIV and/or AIDS patients in home-based care.Method: Unstructured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The research results have revealed that research respondents were rejected, excluded, ill-treated, stigmatised, and discriminated by not only in the community but also by family members and healthcare practitioners. These findings are consistent with experiences of caregivers of people living with other chronic illnesses (Kohli et al, 2012;Van Deventer & Wright, 2017;Ilja et al, 2017). These results further highlighted the lack of knowledge and disregard for the basic human rights of all citizens as enshrined in the South African Constitution.…”
Section: Discussionsupporting
confidence: 84%
“…The research results have revealed that research respondents were rejected, excluded, ill-treated, stigmatised, and discriminated by not only in the community but also by family members and healthcare practitioners. These findings are consistent with experiences of caregivers of people living with other chronic illnesses (Kohli et al, 2012;Van Deventer & Wright, 2017;Ilja et al, 2017). These results further highlighted the lack of knowledge and disregard for the basic human rights of all citizens as enshrined in the South African Constitution.…”
Section: Discussionsupporting
confidence: 84%
“…Reactions to the caregiver’s child status were tied to the discovery of diagnosis and prior knowledge of the parental diagnosis. The findings are consistent with earlier studies that revealed anxiety and sadness in Zimbabwe, 41 isolation and even suicidal ideation in South Africa 21 and among others 3,22,42 in Africa where especially female caregivers intimated guilt, shame, crying among others as their reactions. This similarity is because of the importance and love attached to having a child, especially in African culture.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of caregiving on the well-being of family members has been studied in different communities across the world (Van Deventer & Wright 2017 :2–7). Swaroop et al ( 2013 :30) established that caregiving can be an emotionally and physically draining experience for family members.…”
Section: Discussion Of Findingsmentioning
confidence: 99%